Strategi Dan Tantangan Transformasi Digital Dalam Pengembangan SDM Pendidikan - Inviolata Rogo; Usman Radiana (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
Digital transformation in the development of educational human resources (HR) is a crucial process in the current digital era. This article explores various strategies that can be implemented to accelerate digital transformation in the education sector, as well as the challenges that may be faced during the process. The main strategies discussed include integrating technology in the curriculum, increasing the digital competence of teaching staff, and developing adequate technological infrastructure. In addition, this article also identifies challenges such as resistance to change, budget constraints, and the digital divide that still exists. Through in-depth analysis and case studies, this article offers practical recommendations to overcome these obstacles and ensure the success of digital transformation in educational human resource development. It is hoped that the results of this research can provide guidance for stakeholders in designing and implementing education policies that are more adaptive to technological developments.